Цифровий потенціал банківського ринку - Івашко, Анастасія Олександрівна; Ivashko, Anastasiia Oleksandrivna (Ірпінь, 2023)
З розвитком цифрових та інформаційних технологій значною мірою скорочується дистанція між виробником і споживачем банківських послуг, що істотно загострює міжбаківську конкуренцію, і навіть конкуренцію з глобальними технологічними компаніями.

With the development of digital and information technologies, the distance between the producer and the consumer of banking services is significantly reduced, which significantly exacerbates interbank competition, and even competition with global technology companies
Digital potential of the banking market
Keywords: цифрова економіка; цифрові банківські технології; світовий банківський сектор; інтернет-банкінг; мобільні додатки; digital economy; digital banking technologies; global banking sector; internet banking; mobile applications